Anti-Monopoly and Competition Laws - Impact on the Indian Pharmaceutical Industry - Kaushik, Prerna; Tripathy, Swagat; Sharma, Rishi; Dureja, Harish (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Background: Competition is a process of economic race between market participants to draw clients. The Indian competition law establishment is an early administration. Before the enactment of the Competition Act in May 2002, Monopolistic and Restrictive Trade Practices (MRTP) Act was the active law that managed certain parts of the opposition. Objective: This manuscript highlights the purpose of competition laws for grappling with the monopolies and restrictive trade practices with a particular focus on pharmaceuticals. Conclusion: The Competition Act highlights the main features of new competition law which put back the old MRTP act and also lets in the proscription of anti-competitive treaties, prevention of misuse of dominance and combinations which prove detrimental to the competition in the market.
Keywords: trade related intellectual property rights (TRIPS)